Culture et civilisation en classe de FLE en Algérie - Rezzag Hebla, Zohra; CHAIA, Nour El-Islam (University of Eloued جامعة الوادي, 2024)
يساعد الكتاب المدرسي المتعلمين على الانفتاح على الأفكار ووجهات النظر الجديدة، وقبول الآخرين بثقافتهم. وهذا لا يعزز التفاهم الأفضل بين الثقافات فحسب، بل يعزز أيضا التواصل الأكثر فعالية والعلاقات الأكثر انسجاما في عالم متزايد التنوع والترابط. حاولنا في هذا البحث تحليل المحتوى الثقافي في الكتاب المدرسي للصف الخامس الابتدائي: نحو تثمين الثقافة والحضارة الوطنية. لتجربة الثقافة التي يعكسها هذا الدليل حقًا. لقد اخترنا تحليل محتوى هذا الدليل (نصوص، صور، أسماء...إلخ)، لتحقيق هدف بحثنا. The textbook helps learners to open up to new ideas and perspectives, and to accept others with their culture. This not only promotes better intercultural understanding, but also more effective communication and more harmonious relationships in an increasingly diverse and interconnected world. In this research, we attempted to analyze the cultural contents in the manual 5th A.P school: towards the valorization of national culture. to experience the culture that this manual truly reflects. We chose to analyze the content of this manual (texts, images, names...etc.), in order to achieve the goal of our research.
description de quelques contenus du manuel scolaire de 5éme A.P
Didactique et Langues appliquée
Keywords: الكتاب المدرسي، الثقافة، المحتوى الثقافي، الثقافة الوطنية; school textbook; culture; cultural content; national culture.